Analysis of Soil Physical Properties and Their Implications for Corn (Zea mays L.) Land Management in Pulubala District - Usman, Ledi Diana Putri; Zulzain Ilahude; Mohamad Lihawa (International Journal of Technology and Education Research, 2025)
This study aims to analyze variations in soil physical properties and their implications for corn (Zea mays L.) land management strategies in Pulubala District. This study used a quantitative descriptive survey method on three systematically selected corn land units, with soil sampling at a depth of 0-20 cm for analysis of texture, water content, bulk density, particle density, and porosity in the laboratory. The results showed that points 1 and 3 have a sandy loam texture with a dominant sand content, while point 2 has a clay texture with a dominant clay fraction. The bulk density and porosity values ​​​​illustrate the gradation of soil compaction, where point 1 is relatively looser with high porosity, while points 2 and 3 show lower porosity and indications of compaction that inhibits aeration and root penetration. In terms of management, land with good physical conditions needs to focus on maintaining soil structure, while more compacted land requires intervention in the form of adding organic matter, improving aeration, and regulating drainage to maintain an optimal corn growing environment.